Influence of Salinity on The Growth and Fatty Acids Production of Euglena sp. Local Strain from Dieng Plateau, Indonesia - Amelia, Ria; Budiman, Arief; Nugroho, Andhika Puspito; Suyono, Dr. Eko Agus (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2023)
High salinity is a challenging environmental stressor for organisms to adapt to. In this work, the effects of added NaCl and KCl at various concentrations (0, 100 mM, and 200 mM) for 13 days in the growth medium were investigated in relation to the physiological, morphological, and proximate content of Euglena sp. Utilizing gas chromatography (GC), the amount of fatty acid methyl esters (FAMEs) was determined. Euglena sp. exhibited an obvious decline in growth rate and photosynthetic pigment with increasing salinity. Biomass, protein, carbohydrates had the highest quantities in KCl 100 mM medium, measuring 0.586 ± 0.096 mg/mL, 0.050 ± 0.00017 mg/mL, and 968.091 ± 81.197 mg/mL, respectively. The treatment with 200 mM NaCl had the highest lipid content, with a lipid concentration of 0.42 ± 0.060 mg/mL. After being cultivated in NaCl and KCl at a 200 mM concentration, respectively, the amount of polyunsaturated fatty acids (PUFAs) declined and the amount of saturated fatty acids (SFAs) increased in Euglena sp. The percentage of PUFAs, such as methyl linoleate and methyl linolenate, did not surpass the European B100 biodiesel standard limit of 12% (weight), despite the wide variety of PUFAs. It showed that the use of NaCl and KCl during salt stress significantly increases Euglena sp. biofuel production. For this reason, cultivating Euglena sp. at high salinity is suitable for producing biofuels.